2014
DOI: 10.1007/s40263-013-0135-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Adverse Events Associated with Statins: Epidemiology, Pathophysiology, Prevention and Management

Abstract: Statins, or 3-hydroxy-3-methyl-glutaryl coenzyme A reductase inhibitors, such as lovastatin, atorvastatin, simvastatin, pravastatin, fluvastatin, rosuvastatin and pitavastatin, are cholesterol-lowering drugs used in clinical practice to prevent coronary heart disease. These drugs are generally well tolerated and have been rarely associated with severe adverse effects (e.g. rhabdomyolysis). Over the years, case series and data from national registries of spontaneous adverse drug reaction reports have demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 166 publications
0
34
1
1
Order By: Relevance
“…Since 2012, systematic reviews [5,[29][30][31] and narrative reviews [32][33][34][35] have repeatedly reported a lack of conclusive evidence that statins cause cognitive impairment. A Cochrane review in 2013 found that a mean reduction in LDL-C by 22 % was not associated with worsening of cognitive function [36].…”
Section: The Statin Experiencementioning
confidence: 99%
“…Since 2012, systematic reviews [5,[29][30][31] and narrative reviews [32][33][34][35] have repeatedly reported a lack of conclusive evidence that statins cause cognitive impairment. A Cochrane review in 2013 found that a mean reduction in LDL-C by 22 % was not associated with worsening of cognitive function [36].…”
Section: The Statin Experiencementioning
confidence: 99%
“…However, there are conflicting data suggesting that statins may actually worsen depression [68]. Tuccori et al [69] 14 review that statins may cause many neuropsychiatric "side effects", including depression, irritability, paranoia, alienation, sleep disorders, neurocognitive impairments and muscle weakness. These negative effects of statins could possibly be driven through effects on other pathways, including lipid and serotonin metabolism, the key antioxidant coenzyme Q10 and induction of autoimmune responses [68][69][70].…”
Section: Gaps and Required Improvements: New Treatmentsmentioning
confidence: 99%
“…Tuccori et al [69] 14 review that statins may cause many neuropsychiatric "side effects", including depression, irritability, paranoia, alienation, sleep disorders, neurocognitive impairments and muscle weakness. These negative effects of statins could possibly be driven through effects on other pathways, including lipid and serotonin metabolism, the key antioxidant coenzyme Q10 and induction of autoimmune responses [68][69][70]. Infliximab, a monoclonal antibody directed against TNF with anti-inflammatory and anti-oxidative effects, was recently shown to have antidepressive effects in patients with initially increased CRP levels [71].…”
Section: Gaps and Required Improvements: New Treatmentsmentioning
confidence: 99%
“…Tuccori et al [12] in their review has emphasized occurrence of neuropsychiatric reactions associated with statins like behavioral alterations such as severe irritability, homicidal impulses, threats to others, road rage, depression, violence, paranoia, alienation, antisocial behavior, cognitive and memory impairment, sleep disturbances, and sexual dysfunctions.…”
Section: Discussionmentioning
confidence: 99%